2017
DOI: 10.1016/j.healthpol.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

What women want: Exploring pregnant women’s preferences for alternative models of maternity care

Abstract: Depending on obstetric risk, maternity care may be provided in one of two locations at hospital level: a consultant-led unit (CLU) or a midwifery-led unit (MLU). Care in a MLU is sparsely provided in Ireland, comprising as few as two units out of a total 21 maternity units. Given its potential for greater efficiencies of care and cost-savings for the state, there has been an increased interest to expand MLUs in Ireland. Yet, very little is known about women's preferences for midwifery-led care, and whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 28 publications
2
24
0
3
Order By: Relevance
“…Interestingly, the respondents' independent decision on money spending and seeking health were not found to have any relationship with WTP for pregnancy in this study. This is in contrast to what Fawsitt and colleagues found out that if women were involved in decision-making actively during labour, it increased their willingness to pay more in order to have improvement of maternity services [15]. Mohale and colleagues documented the relationship between women's literacy and improved utilization of maternity care [16].…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, the respondents' independent decision on money spending and seeking health were not found to have any relationship with WTP for pregnancy in this study. This is in contrast to what Fawsitt and colleagues found out that if women were involved in decision-making actively during labour, it increased their willingness to pay more in order to have improvement of maternity services [15]. Mohale and colleagues documented the relationship between women's literacy and improved utilization of maternity care [16].…”
Section: Discussionmentioning
confidence: 87%
“…In Ireland, choice is important to women when it comes to maternity care [ 4 , 14 ]. In particular, they prioritise safety for their baby and the continuity of care over a hospital’s facilities.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they prioritise safety for their baby and the continuity of care over a hospital’s facilities. A qualitative paper found that women who choose private care felt an added sense of security in labour due to the continuity of care with their obstetrician [ 4 ]. The abolition of the private and semi-private packages of care in public hospitals would deny women who have been paying PHI, perhaps for many years, of choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attributes included continuity of care, average waiting time at each antenatal visit, and access to obstetric, anaesthetic and neonatal care. These attributes derived from qualitative research, which is described elsewhere [ 22 ]. The attributes described the ‘typical’ scenario found in a CLU and MLU.…”
Section: Methodsmentioning
confidence: 99%